Analisis Pengembangan Potensi Pariwisata di Kabupaten Nagekeo dalam Mencapai Pariwisata Berkelanjutan: (Studi: Desa Adat Tutubhada, Kabupaten Nagekeo) - Aurelius Siga; Maria M. Lino; Theny I. B. K. Pah (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
The development of culture-based tourism grounded in local wisdom is an important strategy to improve community welfare while preserving cultural and environmental sustainability. Desa Adat Tutubhada in Nagekeo Regency possesses strong cultural and natural tourism potential; however, its management still faces several challenges. This study aims to analyze the implementation of sustainable tourism principles in the development of tourism potential in Desa Adat Tutubhada. The research employed a qualitative approach using a case study method. Data were collected through in-depth interviews, field observations, and documentation, with informants selected purposively, including local government officials, village managers, and indigenous community members. Data analysis was conducted interactively through data reduction, data display, and conclusion drawing, supported by source and technique triangulation to ensure validity. The findings indicate that tourism development in Desa Adat Tutubhada has begun to reflect sustainable tourism principles. The economic aspect is shown through the provision of tourism facilities and the development of local cultural-based enterprises; the socio-cultural aspect is maintained through the strong role of indigenous communities in preserving traditions and cultural values; and the environmental aspect is supported by local wisdom and environmental education. Nevertheless, challenges remain regarding facility quality, tourism promotion, and institutional strengthening. Therefore, enhancing community capacity, improving governance, and strengthening institutional synergy are necessary to achieve optimal and competitive sustainable tourism development.